A novel dietary improvement strategy: examining the potential impact of community-supported agriculture membership. Issue 14 (9th February 2016) - Vasquez, Angie; Sherwood, Nancy E; Larson, Nicole; Story, Mary
Abstract: Objective: To investigate the use of community-supported agriculture (CSA) as an employer-based health promotion intervention. Design: Quasi-experimental study using a convenience sample of employees at three employers. Setting: Participants and controls from three Minnesota employers completed baseline and follow-up health assessments and surveys about their experiences with CSA. Subjects: A total of 324 participants purchased a CSA share and were eligible for study inclusion. Study participants were matched by age, sex, employer and occupation to a non-randomized control group of individuals who did not purchase a CSA share but completed health assessments during the same time frame as the study participants. Results: The majority of participants were female, white, middle-aged and highly educated. The most common reason for purchasing a CSA share was a desire for fresh food, and the majority of participants were satisfied with their experience. Participants reported a significant increase in the number of vegetables present in the household and the frequency of family meals. The frequency of eating out decreased significantly, especially at fast-food restaurants. Participants also reported an increase in the amount and variety of produce consumed. However, health assessment data did not show significant changes in dietary intake, health status or BMI. Conclusions: CSA participation was associated with improvement in some aspects of the household environment and dietary behaviours. Further research is needed to determine whether employer-based CSA interventions may also lead to improvements in dietary intake and health.